Is Pollution a Giffen Good? General-Equilibrium Analysis and Some Policy Implications - Aleksandar Vasilev (Journal of Environmental Management and Tourism, 2019)
This paper takes a simple model with pollution and environmental quality and derives some novel results. In particular, pollution is shown to be a Giffen good. This is a very important finding with clear policy implications, namely that carbon taxes (and pollution permits) are counter-productive, as they lead to increase in pollution, and instead governments should administratively set emission caps.
Keywords: Q2; Q4; Q54; Q58; 330; pollution; carbon tax; Giffen good